2022
DOI: 10.30574/gscbps.2022.20.2.0305
|View full text |Cite
|
Sign up to set email alerts
|

Investigating insecticidal and repellent activity of Momordica charantia, Calotropis gigantea and Cordia curassavica against Oebalus poecilus

Abstract: Oebalus poecilus (paddy bug) is a destructive rice pest in Guyana that is currently controlled with synthetic chemical pesticides. Increasing resistance rates and farmer's overuse of pesticides have resulted in economic and ecological issues for Guyanese rice farmers. Amid growing economic and ecological concerns, this experiment aimed to investigate the use of alternative botanical extracts from the leaves of Momordica charantia (Baan-Carailli), Calotropis gigantea (Madar-Flower) and Cordia curassavica (Black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…There was no documented work cited on the insecticidal activities of Boswellia dalzielii extracts, except for other plants. For instance It have been reported that the average mortalities rates of extracts after 72 hours for Momordica charantia (98.62%), Cordia curassavica (90.25%) and Calotropis gigantea (100%) (Deolall et al, 2022;Rasib et al, 2022) which was greater than our result. Irfan et al, (2022) also reported the methanol extract of P. hysterophorus at 50 mg concentration had 12.3% mortality rate on S. litura larvae which was lower than our findings with Boswellia dalzielii at higher concentration.…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…There was no documented work cited on the insecticidal activities of Boswellia dalzielii extracts, except for other plants. For instance It have been reported that the average mortalities rates of extracts after 72 hours for Momordica charantia (98.62%), Cordia curassavica (90.25%) and Calotropis gigantea (100%) (Deolall et al, 2022;Rasib et al, 2022) which was greater than our result. Irfan et al, (2022) also reported the methanol extract of P. hysterophorus at 50 mg concentration had 12.3% mortality rate on S. litura larvae which was lower than our findings with Boswellia dalzielii at higher concentration.…”
Section: Resultscontrasting
confidence: 67%
“…Similar results were observed in previous studies conducted using different plant extracts. For example Deolall et al, (2022) demonstrated that extracts from three different plants showed insecticidal and repellent activity on Oebalus poecilus. In a work conducted by Irfan et al, (2022), showed the effect of methanol extract of Parthenium hysterophoras and Moringa oleifera leaf extracts on Spodoptera litura insect and the methanol extract was greater than the ethanol and acetone extracts.…”
Section: Resultsmentioning
confidence: 99%